Triglyceride-Glucose Index and Intravenous Thrombolysis Outcomes for Acute Ischemic Stroke: A Multicenter Prospective–Cohort Study - Lin, Sheng-Feng; Hu, Han-Hwa; Chao, Hai-Lun; Ho, Bo-Lin; Chen, Chih-Hung; Chan, Lung; Lin, Huey-Juan; Sun, Yu; Lin, Yung-Yang; Chen, Po-Lin; Lin, Shinn-Kuang; Wei, Cheng-Yu; et al. (Frontiers in Neurology, 2022)
Background: The triglyceride glucose (TyG) index has recently been proposed as a reliable marker of insulin resistance. There is insufficient evidence to verify that the TyG index is correlated with functional outcomes and hemorrhagic transformation and in stroke patients treated with intravenous thrombolysis (IVT). Methods: We designed a multicenter cohort study which enrolled acute ischemic stroke patients treated with IVT between December 2004 to December 2016. The TyG index was divided into tertiles and computed on a continuous scale. Unfavorable functional outcomes were defined by the modified Rankin scale of 3–6 at 90 days, and the incident rates of symptomatic intracranial hemorrhage (SICH) within 36 h of IVT onset were surveyed. Stroke severity was defined as mild (4–8), moderate (9–15), or high (≥16) based on NIHSS scores. Results: Among the 914 enrolled patients, the tertiles of the TyG index were 8.48 for T1, 8.48-9.04 for T2, and 9.04 for T3. T3 showed an increased risk of unfavorable functional outcomes at 90 days (OR: 1.76; P = 0.0132). The TyG index was significantly associated with unfavorable functional outcomes at 90 days (OR: 1.32; P = 0.0431 per unit increase). No association was found between the TyG index and SICH. These findings were applicable for T3 with stroke of moderate (OR, 2.35; P = 0.0465) and high severity (OR: 2.57, P = 0.0440) stroke patients. Conclusions: This study supports the strong association between the increased TyG index and increased unfavorable functional outcomes at 90 days in acute ischemic stroke patients treated with IVT. These findings were found to be robust in patients with moderate and high stroke severity.